Physical Fruit Traits, Proximate Composition, Antioxidant Activity, and Profiling of Fatty Acids and Minerals of Wild Jujube (Ziziphus lotus L. (Desf.)) Fruits from Eleven Moroccan Origins - Hasna Ait Bouzid; El Hassan Sakar; Laila Bijla; Mohamed Ibourki; Ahmed Zeroual; Jamila Gagour; Jamal Koubachi; Khalid Majourhat; Saïd Gharby (Journal of Food Quality)
This study aimed at investigating the effects of geographical origin on physical fruit traits, proximate composition, fatty acid, and elemental profiling of Moroccan wild jujube (Ziziphus lotus) fruits. Likewise, solvent effects on total phenolic content (TPC), total flavonoid content (TFC), tannin content, and antioxidant activity were also studied. Fruits were sampled from eleven sites where the species grows widely across Morocco (Tafraoute, Taroudant, Zagora, Rhamna, Beni Mellal, Zaouit Cheikh, Khenifra, B-Jaad, Lkhmissat, Sidi Hrazm, and Taounat). Physical fruit traits (length, width, and weight), proximate composition, and minerals were investigated. Fatty acid profiling of extracted oil was also evaluated. TPC and TFC as well as antioxidant activity (ABTS, DPPH, and FRAP) were determined on four different extracts, namely, ethanol extract (EE), methanol extract (ME), acetone extract (AE), and water extract (WE). Our outcomes revealed significant differences (p<0.05) among different origins for the measured fruit traits including ash (1.69–2.31%), moisture (2.56–5.69%), proteins (2.63–4.64%), oil (1.59–2.91%) and carbohydrates (86.82–89.20%). The most abundant minerals were K (548.93–828.44 mg/100 g) and Ca (137.50–211.78 mg/100 g). Major fatty acids were oleic acid (50.65 –60.25%), palmitic acid (12.03–18.67%), and linoleic acid (12.63–17.21%). Acetone performed better in terms of TPC (12.77–21.67 mg GAE/g DM), TFC (11.00–18.92 mg QE/g DM), and antioxidant activity using ABTS (22.96–29.32 mg TE/g DM), DPPH (27.96–96.64%), and FRAP (8.37–37.59 mg AAE/g DM). In conclusion, Z. lotus fruit could be considered as a source of carbohydrates and minerals and also natural antioxidants.